Transformasi Pertanian Presisi Berbasis Digital di Indonesia: Tinjauan Sistematis Peluang dan Tantangan - Iwan Patria (Yayasan Literasi Sains Indonesia, 2025)
Precision agriculture has emerged as a key solution to address food security challenges, resource efficiency, and agricultural sustainability in Indonesia. This study aims to analyze the opportunities and challenges of adopting digital applications in precision agriculture through a systematic literature review using the PRISMA approach. Data were obtained from eight scientific articles published between 2021–2025 and one additional relevant supporting article. The findings indicate that digital applications in precision agriculture provide significant opportunities for improving productivity, optimizing input use, and enhancing information access. However, several challenges persist, including low digital literacy among farmers, limited internet infrastructure in rural areas, high technological investment costs, resistance to adoption, socio-economic disparities, and inadequate policy support. Proposed solutions include the development of user-friendly application interfaces, digital literacy training programs, provision of affordable internet access, subsidized devices, cross-sector collaboration, and evidence-based regulatory policies. This review concludes that inclusive, participatory, and sustainable digital transformation is essential to advance agricultural modernization in Indonesia.